Prognosis and response to first-line single and combination therapy in pulmonary arterial hypertension. (August 2014) - Kylhammar, David; Persson, Liselotte; Hesselstrand, Roger; Rådegran, Göran
Abstract Objectives. To investigate survival, treatment escalation, effects of first-line single- and first-line combination therapy and prognostic markers in idiopathic- (IPAH), hereditary- (HPAH) and connective tissue disease-associated (CTD-PAH) pulmonary arterial hypertension (PAH). Design. Retrospective analysis of medical journals from PAH patients at Skåne University Hospital 2000–2011. Results. 1-, 2- and 3-year survival was 87%, 67%, and 54%, respectively, for the entire population, but worse (p = 0.003) in CTD-PAH than IPAH/HPAH. After 1, 2 and 3 years, 58%, 41% and 24% of patients starting on single therapy were alive on single therapy. 37.5% of patients on first-line single therapy received escalated treatment at first follow-up. First-line combination therapy more greatly decreased pulmonary vascular resistance index (PVRI, p = 0.017) than first-line single therapy. Only first-line combination therapy improved (p = 0.042) cardiac index (CI). Higher mean right atrial pressure (MRAP, p = 0.018), MRAP/CI (p = 0.021) and WHO functional class (p < 0.001) and lower 6-min walking distance (6MWD, p = 0.001) at baseline, and higher PVRI (p = 0.008) and lower 6MWD (p = 0.004) at follow-up were associated with worse outcome. Conclusions. We confirm improved survival with PAH-targeted therapies. Survival is still poor and early treatment escalation frequently needed. First-line combination therapy may more potently improve haemodynamics. MRAP/CI may represent a new prognostic marker in PAH.